THE EFFECTIVENESS OF DIRECT AND INDIRECT WRITTEN CORRECTIVE FEEDBACK IN EFL WRITING PERFORMANCE - Ida Farida Sachmadi; Lia Maulia Indrayani; Ryan Hara Permana (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Reading competency is a critical element to be success in learning in university level. This study aims to measure reading proficiency levels of first year students using five-component skills involving measures of (1) vocabulary knowledge, (2) drawing inferences and predictions, (3) knowledge of text structure and discourse organization, (4) identifying the main idea and summarizing skills, and (5) identifying supporting information. The participants are 117 freshmen undergraduate students, 73 students from Nursing Faculty and 44 students from Cultural Sciences Faculty majoring Japanese language enrolled  at the Universitas Padjadjaran in academic year 2016-2017. The data are collected through a reading comprehension pre-test. The results of this study indicate that there is a mixed and wide variation of students reading competency levels when students’ first enter the university and that a significant number of first year entrants are inadequately prepared for university reading.